2018
DOI: 10.1016/j.hrtlng.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative symptom biochemistry between moderate and advanced heart failure

Abstract: Background: We have a limited understanding of the biological underpinnings of symptoms in heart failure (HF). Objectives: The purpose of this paper was to compare relationships between peripheral biomarkers of HF pathogenesis and physical symptoms between patients with advanced versus moderate HF. Methods: This was a two-stage phenotype sampling cohort study wherein we examined patients with advanced HF undergoing ventricular assist device implantation in the first stage, and then patients with moderate H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The absence of symptoms also does not necessarily confer the absence of change in underlying pathogenesis, particularly in advanced CVD. 15 Nevertheless, symptoms have relevance in CVD, particularly in acute coronary syndrome (ACS), heart failure (HF), valvular disorders, stroke, rhythm disorders, and peripheral vascular disease.…”
Section: Symptom Traits and Caveats In Cvdmentioning
confidence: 99%
“…The absence of symptoms also does not necessarily confer the absence of change in underlying pathogenesis, particularly in advanced CVD. 15 Nevertheless, symptoms have relevance in CVD, particularly in acute coronary syndrome (ACS), heart failure (HF), valvular disorders, stroke, rhythm disorders, and peripheral vascular disease.…”
Section: Symptom Traits and Caveats In Cvdmentioning
confidence: 99%
“…For example, a cohort study found that increased myocardial stress, systemic inflammation, and endothelial dysfunction were linked to increased physical symptoms (eg, dyspnea, fatigue, and pain) among individuals with moderate HF. 83 Furthermore, highquality research evidence shows that physical symptoms (eg, dyspnea and/or fatigue) can lead to exercise intolerance; this decrease in exercise capacity is a sign of patients with HF and is strongly associated with reduced QoL. 84 In contrast, anxiety symptoms are linked to elevated levels of C-reactive protein, interleukin (IL-1, IL-6), and interferon-γ.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological factors may also play a key role in the association between HF symptoms and adverse outcomes 81 ; some studies have found evidence for links between symptoms and inflammation. For example, a cohort study found that increased myocardial stress, systemic inflammation, and endothelial dysfunction were linked to increased physical symptoms (eg, dyspnea, fatigue, and pain) among individuals with moderate HF 83 . Furthermore, high-quality research evidence shows that physical symptoms (eg, dyspnea and/or fatigue) can lead to exercise intolerance; this decrease in exercise capacity is a sign of patients with HF and is strongly associated with reduced QoL 84 .…”
Section: Methodsmentioning
confidence: 99%
“…12 This analysis provides insight on how 3 commonly measured biomarkers in HF (NTproBNP, sTNFαR1, and E-selectin) may elucidate a specific group of those with HF who are at higher risk of adverse events associated with HF, such as fluid volume overload and neurohormonal activation. [6][7][8]18 The other 3 biomarkers that were not included in the final model (soluble ST2, adiponectin, and P-selectin) are still of importance to our understating of HF pathogenesis and also were significantly different between classes with medium to large effect sizes. Hence, although our parsimonious approach to modeling entailed using 3 biomarkers, our solution differentiated patients with respect to 6 underlying and intricately related pathogenic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…This was a secondary data analysis of 2 studies whose methods have been described elsewhere. [17][18][19] The participants from each study were combined into 1 single cohort for data analysis. All participants had a confirmed HF diagnosis made by physical examination, were at least 21 years of age, did not have a significant hearing or cognitive disability, were able to comprehend fifth grade English, had not had a mechanical circulatory device or heart transplant, and did not have any other terminal disease that would prevent them from participating in the study.…”
Section: Methodsmentioning
confidence: 99%